Phytoplankton community structure in PB. Soedirman Reservoir, Banjarnegara District, Central Java, Indonesia - SESILIA RANI SAMUDRA; SULTON FASYA ISLAMI; DYAHRURI SANJAYASARI; ABDUL MALIK FIRDAUS; ADINDA KURNIA PUTRI; NABELA FIKRIYYA; AHMAD NAUFAL ATTAQI (Society for Indonesian Biodiversity, 2024)
Abstract. Samudra SR, Islami SF, Sanjayasari D, Firdaus AM, Putri AK, Fikriyya N, Attaqi AN. 2024. Phytoplankton community structure in PB. Soedirman Reservoir, Banjarnegara District, Central Java, Indonesia. Biodiversitas 25: 2161-2169. Panglima Besar (PB) Soedirman Reservoir (formerly known as Mrica Reservoir), located in Central Java, faces ecological pollution due to organic materials from anthropogenic activities. Monitoring reservoir conditions, comprising physical, chemical, and biological parameters, is important for management. In this context, phytoplankton is a biological parameter that can be used to monitor water conditions. Therefore, this study aimed to observe phytoplankton community structure in PB. Soedirman Reservoir, Banjarnegara District, about the abundance, diversity, and dominance index. Sampling was conducted in July and August 2023 at five stations: the inlet, water around, and those free from floating net cages, ponds, and outlet channels. Data analysis included phytoplankton abundance, Shannon Wiener diversity index (H'), and Simpson dominance index (C). The results showed that the number of phytoplankton genera found was 27, with the average abundance in July being 7,083 cells.L-1, and the most abundant class was Bacillariophyceae (54%). The average abundance in August was 59,574 cells.L-1, the most abundant class being Bacillariophyceae (82%). Additionally, the diversity index (H') value ranged from 1.23-2.07 with the moderate pollution category. The dominance index (C) ranged from 0.16-0.33, showing no species dominated.